Chemical, Botanical and Pharmacological Aspects of the Leguminosae - Benjamim, Jaisielle Kelem França; Costa, Karen Albuquerque Dias da; Santos, Alberdan Silva (Pharmacognosy Reviews)
Leguminosae or Fabaceae belongs to the Fabales order and comprises about 727 genera and 19.327 species. It is the largest family on Brazilian soil. Its biodiversity is present in practically the entire vegetal composition, showing its ecological importance in different ecosystems. It is subdivided into six subfamilies (Caesalpinioideae, Dialioideae, Detarioideae, Cercidoideae, Duparquetia idea and Papilionoideae). It has applications in different areas such as food, reforestation, wood industry, ornamentals, forages and herbal medicine. The secondary metabolites of this family are quite diverse, including the class of flavonoids, phenolic acids, tannins, anthocyanins, coumarins, saponins, phytosteroids and terpenoids, making it the second-largest family to be used with therapeutic resources in the world. Studies reveal important bioactive properties related to species, such as: Antioxidant, antimicrobial, antiproliferative, anti-tumor, anti-inflammatory, anti-leishmania, healing, cardioprotective, hypoglycemic, myorelaxant, antiulcerogenic, serine proteinase inhibition, chemoprotective and anti-wrinkles. In this context, this work aims to present a review on the Libidibia ferrea (Mart. ex Tul.) L.P. Queiroz, Inga edulis Mart, Bauhinia purpurea L. Hymenaea courbaril L, Schizolobium parahyba var. amazonicum (Huber ex Ducke) Barneby, Parkia multijuga Benth, Parkianitida Miq., Pterodon emarginatus Vogel and Phanera splendens (Kunth) Vaz species belonging to Leguminosae, approaching its botanical aspects, its occurrence and uses, as well as its chemodiversity and the associated biological activities.
Keywords: Biological Activity; Chemical Composition; Ethnobotanical; Fabaceae; Plant metabolites; Plant metabolomics